2012
DOI: 10.20453/rmh.v18i2.934
|View full text |Cite
|
Sign up to set email alerts
|

Conocimientos, actitudes y prácticas de la medicina basada en evidencias en médicos asistentes y residentes en dos hospitales de Lima-Perú.

Abstract: La incorporación de la Medicina Basada en Evidencias en países en vías de desarrollo plantea dificultades particulares. Suficiente información de cómo se realiza en el Perú no existe. Objetivo: Describir los conocimientos, actitudes y prácticas de la MBE en médicos asistentes y residentes, así como determinar las barreras que perciben para la inserción de esta en nuestro país. Material y Métodos: Diseño: analítico. Instrumento: cuestionario .Lugar: Hospital Arzobispo Loayza y Guillermo Almenara. Población: 104… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…According to a study carried out by physicians in San Bartolomé Hospital in Lima, 80% of them had a favorable predisposition toward evidence-based learning and considered that research evidence was useful in clinical practice [12]. Similar results were observed in Loayza and Almenara National Hospitals in Lima, where most internists specialist and trainees expressed a favorable attitude toward EBM, but considered that EBM had limited dissemination between professionals, making its implementation complicated [13].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…According to a study carried out by physicians in San Bartolomé Hospital in Lima, 80% of them had a favorable predisposition toward evidence-based learning and considered that research evidence was useful in clinical practice [12]. Similar results were observed in Loayza and Almenara National Hospitals in Lima, where most internists specialist and trainees expressed a favorable attitude toward EBM, but considered that EBM had limited dissemination between professionals, making its implementation complicated [13].…”
Section: Discussionmentioning
confidence: 77%
“…In this study, we found that D5 had the lowest scores. There are several barriers to apply EBP that has been described in previous publications, including the difficulty in accessing information in healthcare centers, the lack of hours dedicated exclusively to research in many institutions, the lack of standardized and developed clinical and procedural guidelines for patient care, and the lack of an exclusive place to discuss research results [12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…In Peru, although health professionals seem to have a favorable disposition to learn and apply EBM, they recognize that lack of time, inadequate training, and lack of access to or understanding of the studies are important limitations [ 7 , 8 , 23 ]. In addition, clinical practice in hospitals may not be evidence-based [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a study conducted in 2017 on recently graduated physicians in Lima, Peru, reported that only one-third perceived having very good or excellent competencies to perform searches, critically read studies, or apply evidence to practice [ 6 ]. Other studies conducted among general practitioners, residents, and specialists in Peru also found a low perception of having competencies in different aspects of EBM [ [7] , [8] , [9] ].…”
Section: Introductionmentioning
confidence: 97%